Histopathological study of neoplastic and non-neoplastic lesions of salivary gland: a study at a tertiary care center - Dholiya, Bhavika M.; Gamit, Bhavna N.; Shah , Hiral K. (International Journal of Research in Medical Sciences, 2023)
Background: Salivary gland lesions are highly heterogenous group of disorder. There are no reliable criteria to differentiate benign from malignant lesions on clinical grounds, so histopathological evaluation is essential. Methods: The present study was retrospective study carried out in the department of pathology, Government medical college, Surat from January 2015 to June 2020. Biopsies/specimens were fixed by 10% neutral buffered formalin and processed, embedded in paraffin and sections were cut and stained with hematoxylin and eosin stain. All the slides were reviewed by authors and re-staining of slides and fresh sections of tissue blocks were performed whenever required. Results: Out of 80 cases, 22 were non-neoplastic, 45 were benign and 13 were malignant. In our study most common non neoplastic lesion was chronic sialadenitis. Most common benign lesion was pleomorphic adenoma. Most common malignant lesion was mucoepidermoid carcinoma. Most commonly involved gland was parotid gland. In parotid gland, most common lesions were benign. The overall sex incidence of salivary gland lesions in male was 45% and 55% in females with a male to female ratio of 1:1.2. Conclusions: Thorough knowledge of morphology of salivary gland lesion is helpful in final diagnosis in predicting prognosis, typing, staging and grading of salivary neoplasms.